Influence of NaHCO3 powder on color and roughness of the composite submitted to bleaching and Euterpe oleracea. - Gabriel Aparecido Balter; Tatiane Cristina Dotta; William Custódio; Alma Blasida Concepcion Elizaur Benitez; Vinícius Cappo Bianco; Ana Paula Terossi de Godoi (Universidad de Concepción., 2022)
Aim: This study aims to evaluate the surface roughness and susceptibility to staining of bleached composite resin with 22% carbamide peroxide, as well as the effect of subsequent prophylaxis with NaHCO3 powder. Material and Methods: Forty disk-shaped (2 × 6 mm) specimens of composite resin (Z250 XT) were prepared. Half of the specimens were subjected to bleaching with 22% carbamide peroxide, and the other half were stored in artificial saliva. In sequence, all specimens were immersed in acai juice (Euterpe oleracea) for 4 h for 14 days, and subdivided into two groups. Group 1 samples were subjected to prophylaxis treatment, while group 2 samples were subjected to treatment with artificial saliva. Surface roughness (Ra) and color (ΔE*) were measured after polishing (T0), bleaching (T1), immersion in acai juice (T2), and application of NaHCO3 powder (T3) using a profilometer and a spectrophotometer. Results: Statistical analyses (analysis of variance and Tukey's test, p≤0.05) revealed that regarding color there was statistically significance for the factors in isolation, except for the factor bleaching. For both color and surface roughness there was statistically significant difference for the interaction, except for the interaction between NaHCO3 power and bleaching. Conclusion: The NaHCO3 air-powder polishing decreases the staining of the composite resin; however, it increases the surface roughness. With respect to the color variable, the whitening factor had no significant effect on the tested material; however, it increases surface roughness.